Cognitive Profile and Markers of Alzheimer Disease–Type Pathology in Patients With Lewy Body Dementias. (6th April 2021) - Howard, Erica; Irwin, David J.; Rascovsky, Katya; Nevler, Naomi; Shellikeri, Sanjana; Tropea, Thomas F.; Spindler, Meredith; Deik, Andres; Chen-Plotkin, Alice; Siderowf, Andrew; Dahodwala, Nabila; Weintraub, Daniel; et al.
Abstract : Objective: To determine whether patients with Lewy body dementia (LBD) with likely Alzheimer disease (AD)–type copathology are more impaired on confrontation naming than those without likely AD-type copathology. Methods: We selected 57 patients with LBD (dementia with Lewy bodies [DLB], n = 38; Parkinson disease dementia [PDD], n = 19) with available AD CSF biomarkers and neuropsychological data. CSF β-amyloid1-42 (Aβ42 ), phosphorylated-tau (p-tau), and total-tau (t-tau) concentrations were measured. We used an autopsy-validated CSF cut point (t-tau:Aβ42 ratio > 0.3, n = 43), or autopsy data when available (n = 14), to categorize patients as having LBD with (LBD + AD, n = 26) and without (LBD − AD, n = 31) likely AD-type copathology. Analysis of covariance tested between-group comparisons across biologically defined groups (LBD + AD, LBD − AD) and clinical phenotypes (DLB, PDD) on confrontation naming (30-item Boston Naming Test [BNT]), executive abilities (letter fluency [LF], reverse digit span [RDS]), and global cognition (Mini-Mental State Examination [MMSE]), with adjustment for age at dementia onset, time from dementia onset to test date, and time from CSF to test date. Spearman correlation related cognitive performance to CSF analytes. Results: Patients with LBD + AD performed worse on BNT than patients with LBD − AD ( F = 4.80, p = 0.03); both groups performed similarly on LF, RDS, and MMSE (all p > 0.1). Clinically defined PDD and DLB groups did not differ in performance on any of these measures (all p > 0.05). A correlation across all patients showed that BNT score was negatively associated with CSF t-tau (ρ = −0.28, p < 0.05) and p-tau (ρ = −0.26, p = 0.05) but not Aβ42 ( p > 0.1). Conclusion: Markers of AD-type copathology are implicated in impaired language performance in LBD. Biologically based classification of LBD may be advantageous over clinically defined syndromes to elucidate clinical heterogeneity.